Outcome of Treatment of Anterior Vaginal Wall Prolapse and Stress Urinary Incontinence with Transobturator Tension-Free Vaginal Mesh (Prolift) and Concomitant Tension-Free Vaginal Tape-Obturator - Ashraf Abou-Elela; Essam Salah; Haitham Torky; Sameh Azazy (Advances in Urology)
Objective. It is to assess the feasibility, effectiveness, and safety of transobturator tension-free vaginal mesh (Prolift) and concomitant tension-free vaginal tape-obturator (TVT-O) system as a treatment of female anterior vaginal wall prolapse associated with stress urinary incontinence (SUI). Patients and Methods. Between December 2006 and July 2007, 20 patients with anterior genital prolapse and voiding dysfunction were treated with the transobturator tension-free vaginal mesh (Prolift) and concomitant tension-free vaginal tape-obturator (TVT-O). Sixteen patients had stress urinary incontinence and 4 patients were considered at risk for development of de novo stress incontinence after the prolapse is repaired. All patients underwent a complete urodynamic assessment. All the patients underwent pelvic examination 4–6 weeks after the operation, and anatomical and functional outcomes were recorded. Results. Twenty cystocoeles were repaired: 6 grade II, 12 grade III, and 2 grade IV. There were no vessel or bladder injuries. Eighteen patients had optimal anatomic results and 2 patients had persistent asymptomatic stage I prolapse. Conclusion. These preliminary results suggest that Prolift system offers a safe and effective treatment for female anterior vaginal wall prolapse. However, a long-term followup is necessary in order to support the good result maintenance.